Socioeconomic Status of Eclipta prostrata Linn. (Bhringraj) in the Life of Locals of Kedarnath Shrine, Uttarakhand, India - Semwal, Prabhakar; Painuli, Sakshi; Joshi, Piyush; Chaukiyal, S. P. (Indian Forester, 2017)
No Abstract.